A FRAMEWORK FOR WASTE REDUCTION IN HONEY SUPPLY CHAIN - Yudha, I Made Dwika Parama; Dewa, Parama Kartika; Kurnianingtyas, Maria Chandra Dewi (J@ti Undip: Jurnal Teknik Industri, 2025)
Honey is a key raw material in the traditional medicine industry, processed through a supply chain that involves various stakeholders, such as suppliers, producers, and distributors. However, the management of the honey supply chain faces several challenges, particularly related to waste, including overproduction, excess inventory of raw materials, and defective products. This study aims to develop a framework for reducing waste in the honey supply chain using a Seven Wastes approach to identify problems, conduct root cause analysis through a fishbone diagram, and map the roles and classifications of stakeholders in implementing solutions. The results indicate that waste is caused by various factors, and the roles of stakeholders are classified based on supply chain drivers. This classification includes the management of machine capacity and maintenance at facilities, the implementation of Economic Order Quantity (EOQ), Just-in-Time (JIT), safety stock systems, as well as improvements in raw material quality in inventory management and procurement, and information classification using a forecasting system based on historical data. The implementation of these solutions is expected to optimize supply chain management and reduce waste.